2017
DOI: 10.1021/acs.langmuir.7b00243
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the Hydrogen-Bonding Network of Water Confined in a Polyelectrolyte Brush

Abstract: Water existing in the vicinity of polyelectrolytes exhibits unique structural properties, which demonstrate key roles in chemistry, biology, and geoscience. In this study, X-ray absorption and emission spectroscopy was employed to observe the local hydrogen-bonding structure of water confined in a charged polyelectrolyte brush. Even at room temperature, a majority of the water molecules confined in the polyelectrolyte brush exhibited one type of hydrogen-bonding configuration: a slightly distorted, albeit orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 46 publications
5
44
0
Order By: Relevance
“…For example, it was proven that the local structure of water reorganizes in the vicinity of polyelectrolyte brushes, leading to an enhancement of the hydrogen-bond network. 49 Furthermore, a similar effect on the methanol liquid structure can be obtained by playing with temperature and pressure. 50 This kind of effect might be exploited similarly to how LiCl has been used in our work.…”
Section: Discussionmentioning
confidence: 81%
“…For example, it was proven that the local structure of water reorganizes in the vicinity of polyelectrolyte brushes, leading to an enhancement of the hydrogen-bond network. 49 Furthermore, a similar effect on the methanol liquid structure can be obtained by playing with temperature and pressure. 50 This kind of effect might be exploited similarly to how LiCl has been used in our work.…”
Section: Discussionmentioning
confidence: 81%
“…Compared with bulk water, bound water exhibits unique structural properties, including difficulty freezing, difficult separation, and restricted mobility and solubility, which endow it with unique applications 36 , 40 , 41 . A recent study 42 indicated that the bound water confined in a polyelectrolyte brush exhibited a tight arrangement with a high density, which greatly enhanced the hydrogen-bonded network. The strong hydrogen-bonding structures of water in swollen polymer brushes have been reported to suppress protein adsorption, affording biocompatibility 43 .…”
Section: Introductionmentioning
confidence: 99%
“…We investigated the unique water structure confined in polyelectrolyte brushes by synchrotron-based soft X-ray absorption and emission spectroscopies (XAS and XES, respectively) [ 42 ]. XAS and XES yield element-specific unoccupied and occupied electronic structures to show the local symmetry of hydrogen bonding.…”
Section: X-ray Spectroscopymentioning
confidence: 99%
“…( b ) Soft X-ray absorption spectra of water confined in the polyelectrolyte brush, dry brush measured in vacuum, liquid H 2 O at room temperature, and I h ice. Reproduced with permission [ 42 ]. 2017, American Chemical Society.…”
Section: Figurementioning
confidence: 99%